2016
DOI: 10.1016/j.expneurol.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor alters microtubule targeting agent-induced neurotransmitter release but not MTA-induced neurite retraction in sensory neurons

Abstract: Peripheral neuropathy is a dose-limiting side effect of anticancer treatment with the microtubule-targeted agents (MTAs), paclitaxel and epothilone B (EpoB); however, the mechanisms by which the MTAs alter neuronal function and morphology are unknown. We previously demonstrated that paclitaxel alters neuronal sensitivity, in vitro, in the presence of nerve growth factor (NGF). Evidence in the literature suggests that NGF may modulate the neurotoxic effects of paclitaxel. Here, we examine whether NGF modulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 118 publications
(158 reference statements)
1
16
0
Order By: Relevance
“…This could be due to insufficient duration and /or dose of NGF to reverse these changes. In accordance to these findings it was reported that NGF could induce axonal extension and branching and protect against some of the toxic neuronal sensitivity changes without reversing the morphological changes [40] .…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This could be due to insufficient duration and /or dose of NGF to reverse these changes. In accordance to these findings it was reported that NGF could induce axonal extension and branching and protect against some of the toxic neuronal sensitivity changes without reversing the morphological changes [40] .…”
Section: Discussionsupporting
confidence: 75%
“…ATRA is capable of regulating the expression of not only NGF but also other neurotrphopins, such as ciliary neurotrophic factor, neurotrophin-3, and brain-derived neurotrophic factor, which could participate in nerve regeneration [48] . It might also overlap the disability of NGF to improve the retraction or degeneration of sensory neurons by its effect on Schwann cells as previously mentioned [40] . Moreover ATRA could regulate actin polymerization in microtubules that disturbed by taxol by transcription of the neurotrophin receptor genes [49] .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Immunostaining and quantitative image analysis were performed as previously described [26][27][28] (see Supporting Information for details).…”
Section: Immunostaining and Quantitative Image Analysismentioning
confidence: 99%
“…Mouse nerve growth factor is a cytokine with nerve repair function, its biological function is similar to human nerve growth factor, and it can not only promote the neuron regeneration, survival, proliferation and differentiation, but is also conducive to nerve fiber growth and nerve injury repair [8][9]. In clinical practice, mouse nerve growth factor preparation is widely used in the treatment of diabetic peripheral neuropathy, acute spinal cord injury, optic nerve injury and other neurological lesions [10][11][12], and it is less reported in the rehabilitation treatment after acute cerebral hemorrhage. In the following study, the effect of surgery combined with nerve growth factor preparation treatment of acute cerebral hemorrhage on nerve cytokines and nerve injury was analyzed.…”
mentioning
confidence: 99%